2013
DOI: 10.1001/jamaoto.2013.3906
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid Expansion With Titanium Plate and Screw

Abstract: The retrolingual hypopharyngeal airway space increased with hyoid expansion using titanium plate and screw in our human cadaveric study, measured using CAM. The degree of increase is further augmented with hyomandibular suspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Increased airflow and reduced closing pressure of the upper airway were achieved with expansion hyoidplasty in the canine model. Human cadaveric study also showed the increase of retrolingual hypopharyngeal airway space with hyoid expansion [16]. The greater horn is a significant structure.…”
Section: Discussionmentioning
confidence: 83%
“…Increased airflow and reduced closing pressure of the upper airway were achieved with expansion hyoidplasty in the canine model. Human cadaveric study also showed the increase of retrolingual hypopharyngeal airway space with hyoid expansion [16]. The greater horn is a significant structure.…”
Section: Discussionmentioning
confidence: 83%